2021
DOI: 10.21037/apm-20-985
|View full text |Cite
|
Sign up to set email alerts
|

Study on the relationship between sex hormone changes and erectile dysfunction in patients with chronic prostatitis/chronic pelvic pain syndrome

Abstract: Background: To investigate the relationship between serum sex hormones and erectile dysfunction (ED), changes in erectile function and sex hormones were studied in patients with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS).Methods: A total of 171 patients with CP/CPPS who met the inclusion criteria from January 2016 to June 2019 were retrospectively analyzed. The level of patient's testosterone (TT), estradiol (E2), luteinizing hormone (LH), follicle stimulating hormone (FSH), prolactin (PRL), pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Therefore, High prevalence of ED was found in men with CP/CPPS or LUTS/BPH compared to the general population. Our data determined that the prevalence of ED in patients with CP/ CPPS dominated by LUTS was 24.7% (95 out of 385 patients had ED), which is similar to previous findings (Chung et al, 2012;Tran and Shoskes, 2013;Chen et al, 2015;Fan et al, 2021), indicating that LUTS in CP/CPPS has a negative effect on erectile function.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, High prevalence of ED was found in men with CP/CPPS or LUTS/BPH compared to the general population. Our data determined that the prevalence of ED in patients with CP/ CPPS dominated by LUTS was 24.7% (95 out of 385 patients had ED), which is similar to previous findings (Chung et al, 2012;Tran and Shoskes, 2013;Chen et al, 2015;Fan et al, 2021), indicating that LUTS in CP/CPPS has a negative effect on erectile function.…”
Section: Discussionsupporting
confidence: 91%
“…Chronic prostatitis/chronic pelvic pain syndrome (CP/ CPPS) is a condition featuring multiple symptoms such as persistent and widespread pelvic pain, as well as lower urinary tract symptoms (LUTS) without demonstrable voiding tract infection, which can be accompanied by psychosocial or psychiatric comorbidities, severely decreasing the QoL in men (Krieger et al, 1999;Huang et al, 2020). As the most common type of prostatitis (Fan et al, 2021), CP/CPPS prevalence is estimated at 2.2-13.8% in the male population (Zhang et al, 2016). Erectile dysfunction (ED), defined as the inability to attain and maintain satisfactory erections for adequate sexual performance, is closely correlated to CP/CPPS (Alkan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Erectile dysfunction is a type of male sexual dysfunction and the relationship between erectile dysfunction and prostatitis has been widely studied. Clinical studies have found that about 29% of CP patients have ED and several clinical cohort studies have confirmed that CP is one of the clinical risk factors of ED (Fan et al., 2020). In recent years, some scholars had found that the phenotype of rat corpus cavernosum smooth muscle cells can transfer from contractile type to synthetic type in EAP rats (Wang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%